PENGENDALIAN PERSEDIAAN OBAT DENGAN PENDEKATAN ECONOMIC ORDER QUANTITY - Ganda Sirait (JURNAL REKAYASA SISTEM INDUSTRI, 2019)
Product inventory in pharmacies is one of problem in controlling drug supplies. How to provide an efficientproduct, need the right calculation with the right method. EOQ method shows that there are savings oninventory cost. It is expected in this study was to determine a forecast that the drugs inventory_ control. Theapproach used in this study is quantitative descriptive. Source of data in this research using primery data sourcesobtained directly from the company. Data collection data using documentation and interviews. Data analysis used inthis research using Economic Order Quantity. The forcasting results for ordering efficient drugs in 2019 are: first,Amlodipine 5 mg 10.153 boxes are needed and at a cost of Rp. 12,843,264.00. Second, Simvastatin 20 mg 25.288 boxesare need at the cost of Rp. 30,44,245.00.